Facile and eco-friendly synthesis of Mn2O3 nanoparticles via microwave-assisted glycerol-thermal method - Yadav, Akash; Jha, Ratnesh; Bhatkar, Akash; Gehlot, Bhavika; Kamble, Aditi; Manikandan, Marimuthu; Bhosale, Hritvik; Vaishnav, Vishal; Rathod, Rutik; Umbarkar, Shubhangi; Raja, Thirumalaiswamy; Bhatte, Kushal D. (Journal of Chemical Sciences, 2025)
Microwave-assisted efficient synthesis of nanosized manganese oxide (Mn2O3) is reported using glycerol and manganese acetate. Glycerol in this reported methodology acts as an efficient solvent for this nanomaterial synthesis under microwave radiation. This reported method enables the synthesis of nanosized Mn2O3 without further use of additives, stabilizers, and bases other than glycerol and manganese precursor. Glycerol is a renewable biomaterial derived nonvolatile and nontoxic, safe solvent. It has a high boiling point and dielectric constant, which makes it an ideal solvent for microwave synthesis. The synthesized nanosized Mn2O3 was analyzed by X-ray diffraction (XRD), high-resolution transmission electron microscopy (HRTEM), X-ray photoelectron spectroscopy (XPS), and Raman spectroscopy. We examined the catalytic properties of as-synthesized Mn2O3 for cinnamyl alcohol oxidation to cinnamaldehyde. In this oxidation activity experiment, nanosized Mn2O3 exhibits good conversion and selectivity towards the desired product. We also made an attempt to understand the probable mechanism of nanomaterial formation and found some conclusive evidence to support it. This research methodology is facile, energy efficient, and involves minimum chemicals for synthesis. It makes this reported methodology not only economically attractive but also environmentally friendly, which aligns well with green chemistry principles.
Keywords: Glycerol; green chemistry; Nanosized Mn2O3; nanostructured catalysis